2023
DOI: 10.1186/s12889-023-15442-z
|View full text |Cite
|
Sign up to set email alerts
|

The association between fatty liver index and onset of diabetes: secondary analysis of a population-based cohort study

Abstract: Background According to research, the fatty liver index (FLI) is associated with diabetes. However, few studies have been conducted to investigate the relationship between FLI and diabetes risk from various perspectives. This study comprehensively investigated the relationship between FLI and incident diabetes in a large Japanese population. Methods This retrospective cohort study included 14,280 participants from Murakami Memorial Hospital in Japa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…15,16 A myriad of studies provide evidence that the severity of NAFLD, assessed by the FLI, predicts the development of diabetes. [17][18][19] However, the FLI was initially developed and validated in Western populations, raising concerns about its accuracy in assessing NAFLD among the Asian population. 20 A previous study conducted by our team revealed that the ZJU Index, which comprises four independent risk factors for NAFLD, namely, body mass index (BMI), fasting plasma glucose, triglyceride, and the alanine aminotransferase-to-aspartate aminotransferase ratio, and an adjustment point for females, is a superior predictor of NAFLD in the Chinese population compared to the FLI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 A myriad of studies provide evidence that the severity of NAFLD, assessed by the FLI, predicts the development of diabetes. [17][18][19] However, the FLI was initially developed and validated in Western populations, raising concerns about its accuracy in assessing NAFLD among the Asian population. 20 A previous study conducted by our team revealed that the ZJU Index, which comprises four independent risk factors for NAFLD, namely, body mass index (BMI), fasting plasma glucose, triglyceride, and the alanine aminotransferase-to-aspartate aminotransferase ratio, and an adjustment point for females, is a superior predictor of NAFLD in the Chinese population compared to the FLI.…”
Section: Introductionmentioning
confidence: 99%
“…31 To determine the presence of NAFLD in the Chinese population, our team developed the "ZJU Index" in 2015, with the aim of providing an alternative to ultrasonography and screening patients indicated for CT and MRI. 18 Compared with the Fatty Liver Index (FLI), the ZJU Index offers a comparable level of simplicity, as all its components are easily accessible, and it outperforms the FLI in predicting NAFLD incidence. The exclusion of waist circumference from the ZJU Index has been demonstrated to contribute to its independence across different races and ethnicities, 32,33 whereas the addition of fasting plasma glucose values to the model fosters a closer relationship between NAFLD and T2DM.…”
mentioning
confidence: 99%